Frais chisel Shaft Strength Calculation on the Model in the Laboratory Hydrodynamic - Suyadi Suyadi; Hardi Zen (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2017)
A process process in the manufacture of milling machines Keyway (slot) propeller shaft models - ship propeller is routine work done in BTH-BPPT. The main work in this process requires the use of a standard cutting blade milling (Hight Speed Steel), therefore the technical study on the magnitude of cutting force is needed in predicting the service life of the milling blade. To get the service life of the chisel eye analysis in the process of cutting with a knife cut milling standard (HSS) where the variables selected in this machining processes such as engine speed is very influential parameter to change the style, torque and strain. The results showed that for the process sharpener at rpm 400 rpm and 500 rpm eyes chisel operating under normal conditions, while at rpm 785 rpm chisel eye operating at extreme conditions in which the generated strain of 39.6 Ksi and lifespan chisel 138 operational days 4,5 frais chisel or a calendar month.